Translation and Equivalence: An Argumentative Approach - Damacena, Bianca (International Journal of Linguistics, 2024)
Purpose: This article aims at establishing a dialogue between the Theory of Semantic Blocks (TSB), developed by Ducrot and Carel, and translation theories (the notions of equivalence, skopo, and translators' role), seeking a possible strategy for solving difficult situations when translating humoristic texts that have polysemy or homonymy relations. Methodology: The research methodology involved a literature review, and in the end, a humorous statement containing polysemy was chosen to illustrate how the application of TSB would work in a translation. In this paper, we do not aim to choose the most correct approach but try to match the positive aspects of each one with TSB in order to find strategies that might help translators. Findings: We understood that establishing argumentative meaning for enunciates enables a more proper selection of linguistic entities because it is done based on an argumentative equivalence. This study is ongoing. Given its relatively lengthy nature, it may not be applicable in situations requiring simultaneous translation. Unique Contribution to Theory, Practice and Policy: However, further investigation could explore its use as a means of assessing the adequacy of written translations. A more comprehensive study is also essential to discover additional ways of streamlining the translator's tasks and to determine if TSB can address various translation challenges across different textual genres. In conclusion, studies like this play a crucial role in expanding the range of possibilities to enhance a translator's work. This enables them to navigate between languages and cultures more confidently, linguistically supported, without the need to remain invisible to be recognized as proficient professionals.